Globalization's Contradictions - Conway, Dennis; Heynen, Nik (Taylor & Francis, 2006)
Since the 1980s, globalization and neoliberalism have brought about a comprehensive restructuring of everyone's lives. People are being 'disciplined' by neoliberal economic agendas, 'transformed' by communication and information technology changes, global commodity chains and networks, and in the Global South in particular, destroyed livelihoods, debilitating impoverishment, disease pandemics, among other disastrous disruptions, are also globalization's legacy. This collection of geographical treatments of such a complex set of processes unearths the contradictions in the impacts of globalization on peoples' lives. Globalizations Contradictions firstly introduces globalization in all its intricacy and contrariness, followed on by substantive coverage of globalization's dimensions. Other areas that are covered in depth are: globalization's macro-economic faces globalization's unruly spaces globalization's geo-political faces ecological globalization globalization's cultural challenges globalization from below fair globalization. Globalizations Contradictions is a critical examination of the continuing role of international and supra-national institutions and their involvement in the political economic management and determination of global restructuring. Deliberately, this collection raises questions, even as it offers geographical insights and thoughtful assessments of globalization's multifaceted 'faces and spaces.'